2020
DOI: 10.3390/foods9080967
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cooking on Bioactive Compounds and Antioxidant Activity of Pigmented Rice Cultivars

Abstract: Pigmented rice cultivars, namely Venere and Artemide, are a source of bioactive molecules, in particular phenolics, including anthocyanins, exerting a positive effect on cardiovascular systems thanks also to their antioxidant capacity. This study aimed to determine the total phenol index (TPI), total flavonoids (TF), total anthocyanins (TA) and in vitro antioxidant capacity in 12 batches of Venere cultivar and two batches of Artemide cultivar. The rice was cooked using different methods (boiling, microwave, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The main novelty in our work is to improve the knowledge about pigmented rice, such as Artemide rice, which requires a longer cooking procedure than white rice. The data obtained were not limited to polyphenols variations [ 36 ], but we have also improved the information about the cooking impact on the main nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The main novelty in our work is to improve the knowledge about pigmented rice, such as Artemide rice, which requires a longer cooking procedure than white rice. The data obtained were not limited to polyphenols variations [ 36 ], but we have also improved the information about the cooking impact on the main nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Microwave cooking conserved two- to three-fold higher anthocyanin content in glutinous and non-glutinous rice in comparison to steam cooking [ 119 ]. For Italian purple rice, no anthocyanin reduction was obtained after cooking using either a rice cooker or a water bath [ 120 ]. Similarly, cooking with risotto showed stable cyanidin-3-glucoside content [ 31 ].…”
Section: Stability Of Grain Anthocyanin In Purple Rice During Post-harvest Processingmentioning
confidence: 99%
“…Ito and Lacerda [ 34 ] suggested that anthocyanins and phenolic compounds in black rice provide health benefits. Fracassetti et al [ 35 ] found that cooking pigmented rice cultivars resulted in lower reductions in bioactive compounds than cooking by boiling, microwaving, or pressure cooker. Melini and Acquistucci [ 36 ] reported that cooking pigmented Thai and wild rice induced decreases in bioactive anthocyanins, carotenoids, and phenolic compounds.…”
Section: Resultsmentioning
confidence: 99%